Optimizing property preservation in the USA: a strategic blend of HRM and marketing- a report on Apex DMIT - Shuhim, Sakibul Hossain (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.